Особливості забруднення ґрунтів кадмієм та іншими важкими металами підприємствами кольорової металургії - Яковенко, О.В.; Самчук, А.І.; Кураєва, І.В.; Манічев, В.Й. (Мінералогічний журнал, 2011)
Вивчено забруднені ґрунти навколо підприємств кольорової металургії, визначено вміст кадмію та інших важких металів у них, форми знаходження в цих ґрунтах, сировині та відходах виробництва. Встановлено, що в забруднених ґрунтах метали знаходяться переважно в сорбованій на гідроксидах, органічній і фіксованій формах,
а також значно підвищується вміст рухомих форм важких металів. Изучены загрязненные почвы, определены содержание кадмия и других тяжелых металлов, формы нахождения в данных почвах, сырье и отходах производства. Установлено, что в загрязненных почвах металлы находятся преимущественно в сорбированной
на гидроксидах, органической и фиксированной формах, а также значительно повышается содержание
подвижных форм тяжелых металлов. The polluted soils have been studied for the content of
cadmium and other heavy metals, their forms of occurrence
in the given soils, raw materials and production wastes
have been defined. It is established that metals in the
polluted soils are mainly in the organic and fixed forms
sorbed on hydroxides. The content of mobile forms of
heavy metals considerably increases in the polluted soils.
The pollution of soils is the most dangerous kind of
anthropogenous activity. In the conditions of strengthening
of technogenic loading in the form of emissions and dumps
of polluting substances in the environment it represents
huge danger in the form of accumulation of these
substances in soils and transition from soils to the adjacent
environment. Ecological consequences of pollution directly
depend on concentration of polluting substances and
durability of pollutants binding by soil. Therefore research
of the forms of heavy metals finding in the polluted soils is
an urgent problem. Indicators of mobility of heavy metals
are the most well-founded criteria of geochemical
estimation of the polluted territories.
The structure of chemical compounds of soil causes
reproduction by soil of its ecological functions. The maintenance
of connections of main elements Si, Al, Fe displays
intensity of transformation of primary and formation
of secondary minerals, defines properties of soil as a natural
body. Ecological consequences of soils pollution depend
on distribution of pollutants arriving in soil between soil
components.